2006
DOI: 10.1073/pnas.0506786103
|View full text |Cite
|
Sign up to set email alerts
|

Tumor marker-responsive behavior of gels prepared by biomolecular imprinting

Abstract: We report dynamic glycoprotein recognition of gels prepared by biomolecular imprinting using lectin and antibody molecules as ligands for tumor-specific marker glycoproteins. The glycoproteinimprinted gels prepared with minute amounts of cross-linkers could dynamically recognize tumor-specific marker glycoproteins by lectin and antibody ligands and induce volume changes according to the glycoprotein concentration. The glycoprotein-imprinted gel shrank in response to a target glycoprotein but nonimprinted gel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
165
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(172 citation statements)
references
References 28 publications
(28 reference statements)
0
165
0
2
Order By: Relevance
“…[29][30][31] So far, to the best of our knowledge, the preparation of a thermosensitive polymer to imprint a protein has been limited to static formats, such as our previous study on the bulk polymerization of a macroporous thermosensitive imprinted hydrogel for the recognition of proteins, [32] and has not been applied to monolithic columns for proteins. [33][34][35][36] This study focuses on the combined merits of the monolithic column and the thermosensitive protein MIP to selectively separate a template protein in an on-line method. NIsopropylacrylamide (NIPAAm; a smart material), acrylamide (AAm), and methacrylic acid (MAA) were chosen as monomers to develop a suitable thermosensitive MIP with lysozyme as the template.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] So far, to the best of our knowledge, the preparation of a thermosensitive polymer to imprint a protein has been limited to static formats, such as our previous study on the bulk polymerization of a macroporous thermosensitive imprinted hydrogel for the recognition of proteins, [32] and has not been applied to monolithic columns for proteins. [33][34][35][36] This study focuses on the combined merits of the monolithic column and the thermosensitive protein MIP to selectively separate a template protein in an on-line method. NIsopropylacrylamide (NIPAAm; a smart material), acrylamide (AAm), and methacrylic acid (MAA) were chosen as monomers to develop a suitable thermosensitive MIP with lysozyme as the template.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other separation methods of glycoprotein [42], the imprinted nanospheres had a more satisfied selectivity. The adsorption rate of the imprinted nanospheres was faster than that of tumor marker-responsive gels [43], which can be attributed to the formation of the specific binding sites on the surface of the nanospheres. Moreover, the reusability was superior to that of MIPs by polymerization of 3-aminophenylboronic acid [44].…”
Section: Real Sample Analysismentioning
confidence: 98%
“…Miyata et al in a recently reported article on stimuli-sensitive gels reported dynamic glycoprotein (GP) recognition by gels prepared by biomolecular imprinting [251]. The GPimprinted gels had lectin and antibodies as ligands for tumor-specific marker GPs and were prepared with minute amounts of crosslinkers.…”
Section: 34mentioning
confidence: 99%